STRUCTURE AND DEVELOPMENT OF VIRUSES OBSERVED IN THE ELECTRON MICROSCOPE : II. VACCINIA AND FOWL POX VIRUSES - Morgan, Councilman (The Rockefeller University Press, 1954)
Vaccinia and fowl pox viruses were visualized by the electron microscope in sections of infected chorioallantoic membrane of chicken embryos. The viruses were of similar structure and size, averaging 200 x 300 mµ with considerable individual variation. Intracytoplasmic viral particles contained a dense, nucleus-like body (nucleoid) separated from granular material (viroplasm) by a zone of lesser density. They were enclosed by a single membrane. Near the surface of the host cell and in the extracellular space the particles consisted of a central body of variable shape and density enclosed by a double membrane. The initial sites of development were confined to the cytoplasm of the host cell. Before release from the host cell the viral nucleoids appeared to enlarge and to occupy a central position within the particle, which became enclosed by a double limiting membrane. The brick-shaped forms found after removal of the embedding plastic from thick sections indicated that drying caused characteristic distortion of certain viral particles.